AKSIOLOGI PENGHAFAL AL-QUR'AN: INTERNALISASI NILAI-NILAI AKHLAK MULIA PADA SANTRI PONDOK PESANTREN TAHFIDZUL QUR’AN INSAN KAMIL KARANGANYAR - Aina Mardhiyah; Mujiburrohman (Jurnal Binagogik, 2026)
This study aims to determine how the Pondok Pesantren Tahfidzul Qur’an (PPTQ) Insan Kamil Karanganyar internalizes noble character values into Quran-memorizing students (santri) from the perspective of Islamic axiology. Additionally, this research examines the methods employed by instructors, the behavioral monitoring system, as well as the supporting and inhibiting factors in the field. This study utilizes a descriptive qualitative method with a case study approach. Data were collected through interviews with the Curriculum Coordinator and Tahfidz Instructors, observations of the students’ behavior, and documentation studies, which were then validated using triangulation techniques. The results indicate that the internalization of moral values at this Islamic boarding school has successfully cultivated ten ideal Muslim character traits within the students. Interestingly, improvements in students’ character are not determined by the quantity of their memorization (ziyadah), but rather by the strength of their memorization quality (mutqin) and their diligence in reviewing it (murajaah), which fosters patience and humility. The character-building process is implemented through the study of three classical etiquette books, a strict daily routine from waking up until sleeping, positive role-modeling from the teachers, and an educational reward-and-punishment system. Students’ behavioral development is monitored daily using daily evaluation sheets (mutabaah) and reported through a semesterly character report card. The primary supporting factors for this program include a comfortable boarding school environment and exemplary behavior from the instructors. Meanwhile, the inhibiting factors consist of the students’ dense daily schedule as well as the negative influence of social media and smartphone use during vacations or parent visits.